Risk and financial cost management of injection wells in mature oil fields - Josip Ivšinović; Vjekoslav Pleteš (Journal of Risk and Financial Management, 2021)
Risk and financial cost management are becoming increasingly important in the oil industry, especially in companies that have mature oil fields as assets. In such cases, risk and cost analysis are crucial to their existence. The paper analyzes the risks and costs through the modification of geological probability of success (POS) and obtaining the cost correction coefficient when planning capital investments in injection wells. Mature oil field 'B' in the northern part of the Republic of Croatia was analyzed. For field 'B', these values were calculated: 0.8577 for probability of success for workovers, 0.4824 for modified POS for reservoir flooding, and 1.30 for cost correction coefficient for workovers.
Keywords: 330; risk management; cost management; Croatia; injection wells; mature oil fields; probability of success (POS)